Identifying and Overcoming Obstacles to ESG Integration in Indian Companies: An Exploratory Study - Debnath, Prashant; Chellasamy, P.; Juraij K, Muhammed (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research paper aims to identify and overcome obstacles to ESG (Environmental, Social, and Governance) integration in Indian companies through an exploratory study. The study employs a qualitative research approach. Preliminary results suggest that Indian companies face several obstacles in integrating ESG factors into their decision-making processes, including a lack of awareness or understanding of ESG factors, limited availability of ESG data, weak regulatory frameworks, and cultural or institutional barriers. Potential solutions to these obstacles include increasing awareness through education and training, improving data quality and availability, strengthening regulatory frameworks, and building partnerships between companies and other stakeholders to promote ESG integration. The findings of this study have important implications for Indian companies, investors, regulators, and other stakeholders, by providing insights into the major obstacles to ESG integration in India and identifying strategies to overcome these obstacles